82 POSSIBLE NOVEL BIOMARKER OF ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2020) - Saito, R; Maruyama, S; Shoda, K; Kawaguchi, Y; Akaike, H; Yamamoto, A; Takiguchi, K; Furuya, S; Hosomura, N; Amemiya, H; Sudo, M; Kawaida, H; et al.
Abstract: : Recently, patients with esophageal squamous cell carcinoma (ESCC) have been treated with combination therapy, including surgical resection, chemotherapy, and/or radiation therapy. Therefore, the development of novel and useful biomarkers is expected because the malignant behavior of tumors and the treatment effect vary in each case. In this study, we examined the clinical significance of microRNA-X (miR-X) as a biomarker because it has been reported in studies that examined ESCC cell-lines in vitro. Methods: In all, 81 consecutive patients who underwent radical esophagectomy without preoperative treatment for ESCC were examined. Total RNA was extracted from formalin-fixed paraffin-embedded samples and miR-X expression levels were evaluated. In this process, the miR-X levels were standardized against the RNU6B expression levels and were analyzed using the ΔΔCq method. Clinicopathological features between high and low expression groups of miR-X were compared using the median expression level as the cutoff value. Prognostic analyses were performed using several factors, including miR-X expression levels, to gage the cancer-specific (CSS) and recurrence-free survival (RFS) of these patients. Results: High miR-X expression was found to be significantly related to deep invasion (p < 0.001) and high vascular invasion (p < 0.001). Prognostic analyses demonstrated the suitability of miR-X expression as a significant adverse prognostic factor both in cancer-specific and recurrence-free survival (p = 0.006 & p = 0.004, respectively) of patients. Multivariate analysis using factors such as T- and N-factors, tumor size and miR-X expression levels indicated that the miR-X level was an independent prognostic factor as well as T- factor (CSS, hazard ratio: 2.263, p = 0.034), and T- and N-factors (RFS, hazard ratio: 2.22, p = 0.033). Conclusion: The present study revealed that high miR-X expression was related to deep invasion and high vascular invasion in ESCC. It was also independent adverse prognostic factor for patients with ESCC. Detailed examination including in vitro re-verification is required because these results were inconsistent with previous reports and miR-X might play different roles in clinical settings. In any case, further detailed studies might establish the significance of miR-X as a novel and useful biomarker of ESCC.